Genome-Wide Identification and Expression Profile of the SNAT Gene Family in Tobacco (Nicotiana tabacum) - Zhang, Jiemei; Yao, Zhengping; Zhang, Renjun; Mou, Zongmin; Yin, Honghui; Xu, Tianyang; Zhao, Dake; Chen, Suiyun (Frontiers in Genetics, 2020)
Melatonin plays key roles in the development and confers stress tolerance for plants. Serotonin N-acetyltransferase is either as the last step enzyme or as the penultimate enzyme and one of the rate-limiting enzymes in phytomelatonin biosynthesis. Till now, SNAT genes have not yet been characterized in tobacco, one of the important economic plants. With the Acetyltransf_7 conserved domains as the query sequence, 12 NtSNAT candidate genes were retrieved from the genome of tobacco (Nicotiana tabacum). These NtSANTs were divided into two groups in the phylogenetic tree. NtSANT2 and NtSANT2 were clustered with the typical SNATs, and the remaining 10 NtSANTs were out of SNATs grouped independently. Other 10 NtSNATs only have Motif 1, whereas the representative SNATs, like NtSANT2 and NtSANT2 or the SNAT from cyanobacteria, are with five motifs. Besides, NtSNAT1 and NtSNAT2 have high homology with the characterized OsSNAT1, 62.95%, and 71.36%, respectively, while other 10 NtSANT genes show the low homology with OsSNAT1. To the end, it is hypothesized that NtSANT1 and NtSANT2 are probably tobacco SNAT, and the other 10 candidates could be assigned as the NtSNAT-like genes. Furthermore, Nicotiana tomentosiformis and Nicotiana sylvestris, two diploid ancestors of N. tabacum, both have two SNAT candidates, therefore, it is speculated that the gene rearrangement or deletion in the process of genomic stabilization after the whole-genome duplication or polyploidization leads to the reserve of NtSANT2 and NtSANT2 during the evolution of tobacco from diploid to allotetraploid. NtSNAT and NtSNAT-like genes were differentially expressed in all organs and under different stress conditions, indicating that these genes play a crucial role in plant growth and development and stress resistance. Under different stress conditions, NtSANT1 was significantly up-regulated upon high temperature and cadmium stress, while NtSANT2 did not significantly increase in all stress treatments. These results provide valuable information in elucidating the evolutionary relationship of SNAT genes in tobacco and genetic resources for improving tobacco production in the future.